2013
DOI: 10.1155/2013/562175
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Mixed Infections in a Patient Presenting with Acute Febrile Illness in the Tropics

Abstract: Concurrent infections with more than one etiological agent can result in an illness with overlapping symptoms, resulting in a situation where the diagnosis and management of such a patient could be challenging. We report a case of vivax malaria in a patient who was also serologically positive for leptospirosis and dengue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Although concurrent infection is uncommon, it has subsequently been mentioned with increasing frequency in literature. There were isolated case reports in India [7, 20–24], East Timor [12], Japan [17], Bangladesh [13], Indonesia [14], Malaysia [16], and Cambodia [15]. Following that, a series of cases were reported in French Guiana [25, 26], Brazil [11, 27], India [2830], Bangladesh [31], Pakistan [10], Peru [32], and Kenya [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although concurrent infection is uncommon, it has subsequently been mentioned with increasing frequency in literature. There were isolated case reports in India [7, 20–24], East Timor [12], Japan [17], Bangladesh [13], Indonesia [14], Malaysia [16], and Cambodia [15]. Following that, a series of cases were reported in French Guiana [25, 26], Brazil [11, 27], India [2830], Bangladesh [31], Pakistan [10], Peru [32], and Kenya [33].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first reported case of dengue-malaria co-infection in France in 2005 [6], more cases have been reported in India [7, 8], Pakistan [9, 10], Brazil [11], East Timor [12], Bangladesh [13], Indonesia [14], Cambodia [15], Malaysia [16], and Japan [17]. Among these reported cases, only Plasmodium falciparum and Plasmodium vivax were involved.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Leptospira spp./ DENV co-infections have been reported from Mexico, 16 Barbados, 17 India, [18][19][20][21][22] Pakistan, 23 and Jamaica, 24 although it is unclear if co-infection is more likely to result in death. Here, we report four fatal cases of Leptospira spp./DENV co-infection in Puerto Rico, of which one (Case 1) was previously described.…”
Section: Introductionmentioning
confidence: 99%
“…In a study involving 194 patients with dengue in Thailand, no co-infection with malaria was detected whereas another study involving 1723 consecutive febrile patients in French (2016) showed that in the past decades, there were 36 reported incidences of dengue-malaria co-infection in Asia, of which majority (26 cases) were from India. In Malaysia, there is only one case report of patient co-infected with malaria, dengue and leptospirosis [50]. No study has been published to investigate the lower rate of dengue malaria co-infection in Asia thus far.…”
Section: Co-infectionmentioning
confidence: 99%